School food and nutrition environments in Australian primary schools: A scoping review. - Tina Gingell; Emma Esdaile; Danielle Gallegos (PLoS ONE)
Schools are a key environment which can provide access to food, education and skills to enhance food and nutrition literacy and health and wellbeing of primary school students. This review set out to identify key features of school food and nutrition environments (SFNEs) of Australian primary schools, the barriers and enablers for optimising these features, and the impact of school socio-economic status on these features. Six health databases were searched between August 2021 and October 2024. Articles which met the inclusion criteria (n = 148) were selected for a content analysis using a school-system approach. A quality assessment and an in-depth review was then conducted on articles published post 2019 (n = 71). The content analysis identified 18 SFNE elements which were present within the classroom (n = 1), the classroom but externally-operated (n = 1), the school (n = 4), the school but externally operated (n = 6), and other elements external to the school (n = 6). The in-depth analysis revealed a complex interrelationship between these elements and the actors within these elements (students, parents, school staff, volunteers, organisations, community members, and government). As societal and school expectations evolved, this impacted the SFNE. Numerous enablers and barriers to food and nutrition education, student food consumption, and government and school policies were identified, which could be leveraged to optimise SFNEs. Fewer than a quarter of the articles considered the effect of socio-economic factors on the identified SFNE elements. SFNEs are complex, made up of numerous overlapping structural and relational elements. At the local level, the SFNE of every school is unique and school stakeholders (students, parents, school leaders and teachers) should be centralised in the development of local, contextualised strategies to improve their SFNE. State and national resourcing needs to consider financial support as well as time/capacity, personnel, expertise, and curriculum embedment.